PERAN GURU TERHADAP PENANAMAN PROFIL PELAJAR PANCASILA SISWA KELAS IV SDN KARAWACI 3 KOTA TANGERANG - Tantri Nurul Hayati; Asih Rosnaningsih; Erdhita Oktrifianty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine and describe the role of teachers in instilling the Pancasila student profile of fourth-grade students at SDN Karawaci 3 Tangerang City. This study uses a qualitative research method with a descriptive research type. The data sources in this study were five fourth-grade students, fourth-grade teachers, and parents of SDN Karawaci 3 Tangerang City. Data collection techniques used observation, interviews, and documentation. Data analysis techniques with data reduction, data presentation, and drawing conclusions. And the validity of the data uses technical triangulation. The results of the study explain five indicators of the teacher's role as a demonstrator, the teacher's role as a class manager, the teacher's role as a motivator, the teacher's role as a mediator and facilitator, and the teacher's role as an evaluator have been seen well in their implementation. Likewise, the six indicators of the Pancasila student profile have been well embedded in the dimensions of faith, devotion to God Almighty, and noble character, the dimensions of global diversity, the dimensions of mutual cooperation, the dimensions of independence, the dimensions of critical reasoning, and the dimensions of creativity have been well embedded in students, although the dimensions of mutual cooperation and critical reasoning have not been implemented optimally.